Place-remaking under property rights regimes: A case study of Niucheshui, Singapore - Jieming Zhu; Loo-Lee Sim; Xuan Liu (University of California, Institute of Urban and Regional Development (IURD), 2006)
From the perspective of institutional analysis, this paper evaluates the placeremaking process of Niucheshui in Singapore. Since the 1960s, redevelopment in Niucheshui has been substantially shaped by the property rights regimes over land and buildings. Because property rights are defined by the state through statutory land use planning, compulsory land acquisition, rent control, land leasing and conservation of historical buildings, the redevelopment land market is reined in tightly by the state. Prior to 1960, Niucheshui's built form was largely the product of many private individuals' and communities' initiatives. Those players have faded from the scene since the 1960s, and redevelopment of Niucheshui has become the result of interactions between the state and market forces, though public participation is practiced in the land use planning process. Because the urban land market behaves and performs within an institutional framework, and because property rights are one of the most important institutions, the authors argue that the rhetoric of public participation does not assure incorporation of stakeholders' preferences in the shaping of locality; pluralism and diversity in the built environment must be protected by a diverse structure of land property rights which should be incorporated into the place-remaking process.
Keywords: 330; Kommunalplanung; Bodenrecht; Eigentumsrecht; Singapur